Revisiting the 10th‐Century Eldgjá Eruption: Modeling the Climatic and Environmental Impacts - Herman F. Fuglestvedt; Imogen Gabriel; Michael Sigl; Thorvaldur Thordarson; Kirstin Krüger (Geophysical Research Letters)
Abstract The 10th‐century Eldgjá eruption in Iceland is the largest basaltic flood lava eruption of the Common Era. However, the extent of its impacts is unclear due to limited historical records. Combining volcanology and ice‐core analyses from both recent and earlier studies, we present a gas emissions scenario for the Eldgjá eruption spanning 937 to 940 CE, co‐injecting volcanic sulfur and halogens. The combined tropospheric and stratospheric sulfur emissions are 3–8 times higher than those adopted for Eldgjá in existing paleoclimate simulations. Earth system modeling of this scenario under pre‐industrial conditions reveals a compound event with maximum northern extratropics surface cooling of ∼2°C in summer‐autumn of 939 and 940 CE, prolonged Arctic sea ice growth, and large‐scale precipitation changes, concurrent with stratospheric ozone depletion and elevated pollution. These results imply that the combined climatic and environmental effects of the Eldgjá eruption may have significantly impacted human populations at the time.